The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.18632/oncotarget.2857
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells are resistant to carbon ion radiotherapy

Abstract: Mesenchymal stem cells (MSCs) participate in regeneration of tissues damaged by ionizing radiation. However, radiation can damage MSCs themselves.Here we show that cellular morphology, adhesion and migration abilities were not measurably altered by photon or carbon ion irradiation. The potential for differentiation was unaffected by either form of radiation, and established MSC surface markers were found to be stably expressed irrespective of radiation treatment. MSCs were able to efficiently repair DNA double… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 45 publications
3
35
0
Order By: Relevance
“…While it has been reported that MSCs are highly resistant to apoptosis after exposure to various forms of DNA‐damaging agents, treatment with the alkylating agent busulfan induced apoptosis in MSCs; a comparison between bone marrow‐derived MSCs (bmMSCs) and adipose tissue‐derived MSCs (adMSCs) demonstrated significantly higher apoptosis levels in bmMSCs . The regulation of apoptosis in MSCs depends on the expression of anti‐apoptotic proteins in these cells, and the evasion of apoptosis observed in MSCs may depend on paracrine signaling within the stem cells' microenvironment rather than DNA damage repair of individual cells . This is in line with the reported in vivo resistance of MSCs to alkylating antineoplastic drugs.…”
Section: Effects Of Chemotherapeutic Anti‐cancer Agents On Mscsmentioning
confidence: 99%
“…While it has been reported that MSCs are highly resistant to apoptosis after exposure to various forms of DNA‐damaging agents, treatment with the alkylating agent busulfan induced apoptosis in MSCs; a comparison between bone marrow‐derived MSCs (bmMSCs) and adipose tissue‐derived MSCs (adMSCs) demonstrated significantly higher apoptosis levels in bmMSCs . The regulation of apoptosis in MSCs depends on the expression of anti‐apoptotic proteins in these cells, and the evasion of apoptosis observed in MSCs may depend on paracrine signaling within the stem cells' microenvironment rather than DNA damage repair of individual cells . This is in line with the reported in vivo resistance of MSCs to alkylating antineoplastic drugs.…”
Section: Effects Of Chemotherapeutic Anti‐cancer Agents On Mscsmentioning
confidence: 99%
“…Therefore, additional functional features are used to characterize MSCs, among them the cells' fibroblast-like spindle shape, the ability to adhere to plastic surfaces and their differentiation potential along the ostogenic, adipogenic and chondrogenic lineages [2,7]. Several publications have demonstrated a relative radioresistance for MSCs (reviewed in [8]); and the defining stem cell properties have been shown to remain unaffected even by high doses of ionizing radiation [9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Thus, knowledge regarding the effect of IR on tissue-resident MSC is crucial and well-investigated for bmMSC, adipose tissue MSC (adMSC) and umbilical cord MSC (ucMSC). [29][30][31][32][33][34][35][36][37][38][39][40] As a therapeutic approach, study groups applied MSC for tissue regeneration in patients with diabetic ulcer and necrotic osteolysis. 41,42 In contrast, little is known about IR-sensitivity of MSC derived from mucosa of the head and neck region or the parotid gland.…”
Section: Discussionmentioning
confidence: 99%